Lymphatic malformations: A proposed management algorithm - Oosthuizen, J.C.; Burns, P.; Russell, J.D. (International journal of pediatric otorhinolaryngology, 2010)
The aim of this study was to develop a management algorithm for cervicofacial lymphatic malformations, based on the authors’ experience in managing these lesions as well as current literature on the subject. A retrospective medical record review of all the patients treated for lymphatic malformations at our institution during a 10-year period (1998–2008) was performed. Data collected: age at diagnosis, location and type of lesion, radiologic investigation performed, presenting symptoms, treatment modality used, complications and results achieved. 14 patients were identified. Eight (57%) male and six (43%) female. There was an equal distribution between the left and right sides. The majority (71%) of cases were diagnosed within the first year of life. The majority of lesions were located in the suprahyoid region. The predominant reason for referral was an asymptomatic mass in 7 cases (50%) followed by airway compromise (36%) and dysphagia (14%). Management options employed included: observation, OK-432 injection, surgical excision and laser therapy. In 5 cases (36%) a combination of these were used. Historically surgical excision has been the management option of choice for lymphatic malformations. However due to the morbidity and high complication rate associated this is increasingly being questioned. Recent advances in sclerotherapy e.g. OK-432 injection have also shown significant promise. Based on experience in managing these lesions as well as current literature the authors of this paper have developed an algorithm for the management of cervicofacial lymphatic malformations.